Formal aspects of security and trust : 8th International workshop, FAST 2011, Leuven, Belgium, September 12-14, 2011. Revised selected papers - Datta, Anupam; Etalle, Sandro; Barthe, Gilles (Lecture Notes in Computer Science, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 8th International Workshop on Formal Aspects of Security and Trust, FAST 2011, held in conjunction with the 16th European Symposium on Research in Computer Security, ESORICS 2011, in Leuven, Belgium in September 2011. The 15 revised full papers presented together with 2 invited papers were carefully reviewed and selected from 42 submissions. The papers focus on security and trust policy models; security protocol design and analysis; formal models of trust and reputation; logics for security and trust; distributed trust management systems; trust-based reasoning; digital assets protection; data protection; privacy and ID issues; information flow analysis; language-based security; security and trust aspects of ubiquitous computing; validation/analysis tools; web service security/trust/privacy; grid security; security risk assessment; and case studies.